Os direitos humanos e as aporias do consenso - Rocha, Acílio da Silva Estanqueiro (2014)
Direitos Humanos, Vitoria (Francisco de), Las Casas (Bartolomé de), Vieira (António), Suárez (Francisco), Locke (John), Montesquieu, Rousseau (jean-Jacques), Habermas (Jürgen), Lyotard (Jean-François), Rancière (Jacques), Mouffe (Chantal).